Disconnected : haves and have-nots in the information age - Wresch, William, 1947- (New Brunswick, N.J. : Rutgers University Press, 1996)
"In the Information Age, information is power. Who produces all that information, how does it move around, who uses it, to what ends, and under what constraints? Who gets that power? And what happens to the people who have no access to it?" "With vivid anecdotes and data, William Wresch contrasts the opportunities of the information-rich with the limited prospects of the information-poor. Surveying the range of information - personal, public, organizational, commercial - that has become the currency of exchange in today's world, he shows how each represents a form of power. He analyzes the barriers that keep people information-poor: geography, tyranny, illiteracy, psychological blinders, "noise," crime. Technology alone, he demonstrates, is not the answer. Even the technology-rich do not always get access to important information - or recognize its value." "Wresch spells out the grim consequences of information inequity for individuals and society. Yet he ends with reasons for optimism and stories of people who are working to pull down the impediments to the flow of information."--Jacket
Includes bibliographical references (pages 249-257) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Information technology; Information technology -- Social aspects; Information society; Electronic data processing; Technologie de l'information.; Technologie de l'information -- Aspect social; Société de l'information.; information technology; SOCIAL SCIENCE -- Anthropology -- Cultural; POLITICAL SCIENCE -- Public Policy -- Cultural Policy; SOCIAL SCIENCE -- Popular Culture; Electronic data processing; Information society; Information technology; Information technology -- Social aspects; Informatievoorziening; Maatschappij; Ongelijkheid; Culturele verschillen; Vooroordelen; Afrika; Ciencia da informacao; Electrical & Computer Engineering; Engineering & Applied Sciences; Information Technology